Churchill and de Gaulle : the geopolitics of liberty - Morrisey, Will (Rowman & Littlefield, 2014)
This book compares Churchill and de Gaulle as they thought, spoke, and acted through two world wars and the subsequent Cold War. Although the world is very different now, this nuanced history shows how thinking along with these giants of the twentieth century as they responded to the crises of their time will make us more thoughtful citizens today.